Revisiting hospitality internship practices: A holistic investigation - Theocharous, Antonis L.; Zopiatis, Anastasios (My University, 2013)
Hospitality internships are integral part of almost all reputable hospitality programs worldwide. Despite their universal recognition as an essential component of hospitality education, their value is often superseded by the challenges facing hospitality stakeholders in providing such an experience for the next generation of hospitality professions. The purpose of this paper is to investigate—with the utilization of structural equation modeling and after a thorough investigation of the existing literature—the causal relationships of the key issues that define modern hospitality internships and the practice's perceived impact on students' intention to pursue a hospitality career upon graduation. Crucial elements before, during, and after the experience were accounted for, as well as students' overall internship perceptions. Findings prove to be of considerable interest to hospitality stakeholders by confirming some theoretical notions pertaining to the efficacy of the practice, as well as by enhancing understanding and opening new research horizons for those wishing to advance our collective knowledge of the experience.
Keywords: Internships; Hospitality students; SEM